Troops Preparation Policy On A World Peace Mission - Rujito Dibyo Asmoro; Guntur Saputro; T.S. Lumban Toruan; Syaiful Anwar; Luhut Simbolon (Green Publisher Indonesia, 2024)
Indonesia’s involvement in peacekeeping missions has long been a key part of its foreign policy, contributing to world peace as outlined in Republic of Indonesia Law Number 37 of 1999 concerning Foreign Relations. This study aims to analyze the government's policy implementation regarding troop preparation for world peace missions, particularly in relation to Indonesia's role as a Troops Contributing Country (TCC) to the United Nations (UN). The research utilizes a qualitative descriptive approach to understand the intricacies of the troop preparation process through George Edward III's policy implementation model, which emphasizes the importance of disposition, communication, resources, and bureaucracy. Data were collected through document analysis, interviews, and observation of relevant practices in Indonesian military operations. The findings highlight that the personnel selection process for peacekeeping missions is highly structured, requiring compliance with rigorous standards set by both the Indonesian government and the UN. The pre-deployment training, supervised by the TNI (Indonesian National Army) Headquarters, ensures that selected personnel are adequately prepared for their assignments. This comprehensive preparation includes mental and physical readiness, as well as the necessary technical and language skills. The results also emphasize the importance of strong inter-agency coordination, particularly between the Ministry of Defense and the Ministry of Foreign Affairs, to ensure the success of these missions. Furthermore, the study reveals that budgetary and resource constraints remain significant challenges in sustaining peacekeeping operations. In conclusion, Indonesia's contribution to global peacekeeping missions underscores the nation's commitment